ANALISA PEMILIHAN PENYEDIA JASA PELAKSANA KONSTRUKSI PEMERINTAH SUMBER DANA PINJAMAN/HIBAH BANK DUNIA - Felleps Wuisan; Lucia I.R. Lefrandt; Audie L. E. Rumayar; Grace Y. Malingkas (STKIP PGRI Situbondo, 2023)
The implementation of the implementation of the Selection of Construction Work Providers through Public Auction/Direct Selection with Postqualification The National Competitive Bidding (NCB) method is still very rarely used both in ministries and institutions, especially in local governments. Moreover, socialization of this regulation is fairly rare, causing limited information from relevant stakeholders in its implementation, while there are some substantive differences which must be considered and must be implemented. This condition causes the potential implementation of the rugulation is not in accordance with the provisions and causes negative impacts in the implementation of the work/project carried out due to the unpreparedness of the relevant parties. Dominant faktors and correlations to the level of readiness of Stakeholders in the context of implementing the Selection of Construction Work Providers through Public Auction/Direct Selection with Postqualification One Cover Method (National Competitive Bidding/NCB) with. manner. analyze the faktors in the selection of the provider. alone, all at once. Measure .level. readiness of Stakeholders regarding the application of methods. The selection of this provider needs to be done. The research was reviewed in terms of variabel salalt steeped and explained valralibel malsal lallu in a period called the qualitative descriptive method by using falktor alnallisis in correlational alnallysis.